2004
DOI: 10.1007/s00221-004-2106-8
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of increased neuromotor noise for reaching movements in persons with stroke

Abstract: Understanding stroke-induced changes to the motor control of the more affected arm of people with stroke may lead to more effective rehabilitation interventions that improve function. Reaching movements of the more affected arm in persons with stroke are slow, segmented and indirect. Such changes may be related to a reduced capacity to transmit motor commands in the presence of neuromotor noise. In tasks requiring both speed and accuracy, transmission capacity can be characterized by the linear relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 49 publications
3
82
1
Order By: Relevance
“…In this case, joint stiffness is a function of both the limb's position in joint space and the activations of mono-and bi-articular muscles, all of which are functions of time. Previous work 67 has demonstrated that an integrable pseudo-inverse of the Jacobian in the form # = −1 ( −1 ) −1 (7) gives a unique solution to the inverse kinematic problem of redundant robots. (7) is a form of generalized inverse where −1 enters as a quadratic form "weighting matrix".…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, joint stiffness is a function of both the limb's position in joint space and the activations of mono-and bi-articular muscles, all of which are functions of time. Previous work 67 has demonstrated that an integrable pseudo-inverse of the Jacobian in the form # = −1 ( −1 ) −1 (7) gives a unique solution to the inverse kinematic problem of redundant robots. (7) is a form of generalized inverse where −1 enters as a quadratic form "weighting matrix".…”
Section: Discussionmentioning
confidence: 99%
“…7 The simulations were guided by experimentallymeasured reach kinematics, which we analyzed using a non-parametric inverse-normal-transform (INT; 59) Rank Transformation test (RT Type 1; 60) applied to selected structural components of the endpoint jerk. In the INT-RT1 test, the entire set of observations for a given dependent variable is first ranked from smallest to largest, with the smallest observation having rank 1, the second smallest rank 2, and so on (average ranks are assigned in case of ties).…”
Section: Statistical Hypothesis Testingmentioning
confidence: 99%
See 3 more Smart Citations